2014
DOI: 10.1093/mnras/stu1139
|View full text |Cite
|
Sign up to set email alerts
|

The effect of accretion on the measurement of neutron star mass and radius in the low-mass X-ray binary 4U 1608−52

Abstract: Spectral measurements of thermonuclear (type-I) X-ray bursts from low mass X-ray binaries have been used to measure neutron star (NS) masses and radii. A number of systematic issues affect such measurements and have raised concerns as to the robustness of the methods. We present analysis of the X-ray emission from bursts observed from 4U 1608-52 at various persistent fluxes. We find a strong dependence of the burst properties on the flux and spectral hardness of the persistent emission before burst. Bursts occ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
178
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(197 citation statements)
references
References 50 publications
14
178
2
Order By: Relevance
“…Our results are compatible with some of the present predictions. Both hadronic and hybrid star radii of 1.4 M are above 12.8 km, within the observations of the objects BNS 4U 1608−522 [61], BNS SAX J1748.9−2021 [62,63], and RP-MSP PSR J0437−4715 [64,65], but out of the range 10.1-11.1 km obtained in [66], from the analysis of spectroscopic radius measurements of twelve neutron stars obtained during thermonuclear bursts or in quiescence. However, in [67], it was shown that in order to prevent the EOS from violating causality, the radius should satisfy R 1.4 10.7 km, if it is imposed that the EOS also describes a 2 M star.…”
Section: Discussionsupporting
confidence: 84%
“…Our results are compatible with some of the present predictions. Both hadronic and hybrid star radii of 1.4 M are above 12.8 km, within the observations of the objects BNS 4U 1608−522 [61], BNS SAX J1748.9−2021 [62,63], and RP-MSP PSR J0437−4715 [64,65], but out of the range 10.1-11.1 km obtained in [66], from the analysis of spectroscopic radius measurements of twelve neutron stars obtained during thermonuclear bursts or in quiescence. However, in [67], it was shown that in order to prevent the EOS from violating causality, the radius should satisfy R 1.4 10.7 km, if it is imposed that the EOS also describes a 2 M star.…”
Section: Discussionsupporting
confidence: 84%
“…During outburst, KS1731−260 displayed photospheric radius expansion (PRE) bursts (Muno et al 2000). PRE bursts are thought to reach the Eddington luminosity; thus fitting the blackbody emission from the burst can lead to both mass and radius constraints (both the Eddington luminosity and observed emitted radius depend on M and R), assuming the distance to the source is known (Özel 2006, though see, e.g., Poutanen et al 2014 for an opposing view). Özel et al (2012) applied this technique to KS1731−260, implying R12.5 km and M2.1 M e (95% confidence level).…”
Section: Discussionmentioning
confidence: 99%
“…Worpel et al (2013) proposed that the persistent emission intensity would be enhanced during photospheric radius expansion bursts [20]. Subsequently, the enhanced persistent emission were reported in many papers [7,18,13,12,10]. The burst duration is usually very short, preventing us from studying the coronal spectra directly.…”
Section: Discussionmentioning
confidence: 99%